C1q/Tumor Necrosis Factor-Related Protein 9: Basics and Therapeutic Potentials - Guan, Hua; Wang, Yanli; Li, Xiangyu; Xiang, Aoqi; Guo, Fengwei; Fan, Jianglin; Yu, Qi (Frontiers in Physiology, 2022)
C1q/tumor necrosis factor-related protein 9 (CTRP9) is a newly discovered adipokine that is the closest paralog of adiponectin. Proteolytic cleavage of CTRP9 leads to the release of the globular domain (gCTRP9), which serves as the major circulating subtype. After binding with adiponectin receptor 1 (AdipoR1) and N-cadherin, CTRP9 activates various signaling pathways to regulate glucose and lipid metabolism, vasodilation and cell differentiation. Throughout human development and adult life, CTRP9 controls many biological phenomena. simultaneously, abnormal gene or protein expression of CTRP9 is accompanied by a wide range of human pathological phenomena. In this review, we briefly introduce CTRP9 and its associated signaling pathways and physiological functions, which may be helpful in the understanding of the occurrence of diseases. Moreover, we summarize the broader research prospects of CTRP9 and advances in therapeutic intervention. In recent years, CTRP9 has attracted extensive attention due to its role in the pathogenesis of various diseases, providing further avenues for its exploitation as a potential biomarker or therapeutic target.